Procedural status of participants in criminal proceedings as a means of securing rights and legitimate interests - O. Ye. Solovyova (Bulletin of Kharkiv National University of Internal Affairs)
The concept of procedural status of participants in criminal proceedings is considered. According to the Criminal Code of Ukraine, participants in criminal proceedings are parties to criminal proceedings, persons who take part in criminal proceedings. A comparison of this definition with specific norms of the Criminal Procedure Code of Ukraine, which refer to participants in criminal proceedings, shows that the law includes not only persons involved in criminal proceedings, but also the subjects of criminal procedural activity themselves, i.e. officials and bodies that conduct (investigate) criminal proceedings, etc.